Evaluating the Environmental Impacts of Thermoplastic Based-Product Manufacturing Using Life Cycle Assessment (CML-IA Midpoint) - Rahmad Firnandi; Tanti Utami Dewi; Rizka Amalia; Mirna Apriani (Universitas Diponegoro, 2026)
The rapid growth of thermoplastic manufacturing in Indonesia, particularly in thermoplastic-based products such as children’s toys, has not been accompanied by sufficient environmental assessment, especially Life Cycle Assessment (LCA). While previous studies have mainly focused on extrusion processes, this study incorporated additional processes, such as spray coating, to provide a more representative evaluation. This study evaluated the environmental impacts of vacuum cleaner manufacturing using LCA with the CML-IA midpoint method. The data were processed using OpenLCA 2.4.1 and the ELCD database. The results indicate that producing one unit of a vacuum cleaner contributes to multiple environmental impact categories, including acidification (0.001 kg SO₂-eq), eutrophication (0.0001 kg PO₄³⁻-eq), Freshwater Aquatic Ecotoxicity (0.001 kg 1,4-DB eq), and Global Warming Potential (4.208 kg CO₂-eq). Additional impacts were identified in Human Toxicity (0.406 kg 1,4-DB eq), Marine Aquatic Ecotoxicity (2558.698 kg 1,4-DB eq), Photochemical Oxidation (0.000025 kg C₂H₄-eq), and Terrestrial Ecotoxicity (0.041 kg 1,4-DB eq). Among these, Marine Aquatic Ecotoxicity emerged as a dominant contributor because of the presence of hydrogen fluoride released into the environment during the spraying process. To address this issue, mitigation measures, such as substituting inorganic paints in the spray coating process with organic or ecolabel-certified alternatives, have been proposed